Digestibilidade e Ganhos em Peso de Ovinos Alimentados com Diferentes Fontes de Volumosos e Recebendo Somatotropina Recombinante Bovina (rBST) - Ezequiel, Jane Maria Bertocco [UNESP]; Sancanari, Juliana Borsari Dourado [UNESP]; Sampaio, Alexandre Amstalden Moraes [UNESP]; Kronka, Sérgio Nascimento [UNESP]; Ferro, Jesus Aparecido [UNESP]; Ferro, Maria Inês Tiraboschi [UNESP]; Macari, Marcos [UNESP]; Da Silva, Fernanda Pereira (My University, 1999)
The objective of this work was to evaluate the effect of the administration of 20 mg of slow liberation bovine somatotropin (rBST) on the dry matter intake and on the digestibility coefficient of dry matter (MS), acid detergent fiber, crude protein, crude energy, nitrogen balance and the daily weight gain in lambs fed diets based on corn silage, sugar cane or hydrolyzed bagasse and concentrate. Twenty-four crossbred lambs, averaging 4-5 months of age and 22 + 2 kg LW, were used. There was no effect of the rBST on the dry matter intake, the digestibilities of crude protein, acid detergent fiber, the nitrogen balance and the daily weight gain of the lambs. The gross energy digestibility was affected by the rBST administration when different forages or periods post hormonal administration were considered, however, the effect of the hormonal action was observed only on the dry matter digestibility of corn silage diets.
Digestibility and Live Weight Gain of Lambs Fed Different Forages and Administration of Recombinant Bovine Somatotropin (rBST)
Keywords: Corn silage; Digestibility; Growth hormone; Hydrolyzed bagasse; rBST; Sheep; Sugar cane